Selçuklu-Hilafet Münasebetlerinde Bir Dönüm Noktası: Halife El-Müsterşid'in Katli Meselesi - (:unkn) unknown (My University, 2004)
0

After the death of the Caliph al-Mustazhir in 1118, his young and dynamic son al-Mustarshid succeeded to the throne of the Caliphs. The young Caliph strove to restore the temporal and political power of the Abbasid Caliphs, but he was finally defeated and captured by the Saljuq prince Mas'üd near Kirmânşhâh (24 June 1135). Al-Mustarshid was killed by an Ismâ'ilî group on 29th August, 1135 near the city of Marâgha. What at first appeared to be merely a classic case of Ismâ'îlî assasination, was to become a turning-point in the relations between the Saljuqs and the Caliphate. This article re-interprets historical sources in order to place Saljuq-Caliphate relations in a new perspective, and to suggest what the role of the Saljuq dynasty was in the assasination of the Caliph.
Keywords: Tarih